Interactions of the prospective one and the rights among generations for a sustainable human atmosphere - Armas Morales, Carlos E. (2014)
The topic of the prospective one involves a new necessity of the administrations, be these public or private, to prepare with efficiency and effectiveness, the institutional strategic positions, before such a complex world and with prevalence of the uncertainty.In this case we have wanted to interrelate the prospective one (the future) with the, problems of global or word nature, trying to show and to alert to the new generations, the planet that they will receive in relations to the atmosphere and their problem, just as the climatic change hurried by the man, among others of global nature, in such a way that they make today what corresponds them, to live future but human.